A Biomass‐Ligand‐Based Ru(III) Complex as a Catalyst for Cycloaddition of CO2 and Epoxides to Cyclic Carbonates and a Study of the Mechanism. Issue 4 (14th December 2022) - Mao, Haifang; Guo, Manli; Fu, Hongqing; Yin, Kun; Jin, Miaomiao; Wang, Chaoyang; Zhao, Yun; Dong, Zhenbiao; Liu, Jibo
Abstract: Aiming highly efficient conversion of greenhouse gas CO2 to cyclic carbonates, a biomass Ru(III) Schiff base complex catalyst (SalRu ) was constructed by employing a derivative of Lignin degradation (5‐aldehyde vanillin). The SalRu catalyst had a remarkable conversion for epoxides into corresponding cyclic carbonates even at atmospheric pressure of CO2 without the presence of co‐catalyst. As the condition at 120 °C and 2 MPa CO2 the conversion reached to 94 % with selectivity at 99 % after 8 h. 32 % cyclic carbonate production was obtained even under 0.2 MPa CO2 pressure. The epoxide activation and ring opening, CO2 insertion and cyclic carbonate formation were illuminated explicitly through the of characteristic absorption peaks changing, which further providing direct and visual evidence for the mechanism proposing. This study has important theoretical significance for the comprehensive utilization of environmental pollutants and energy. Abstract : A Ru(III)Salen organic complex was designed and prepared for the cycloaddition reaction of CO2 and various epoxides without the presence of co‐catalyst. The catalyst showed excellent compatibility with the cycloaddition reaction of epoxides and CO2 .